Sex, Age, Behavior, and School Subject as Determinants of Report of Learning Problems. - Caplan, Paula J. (Journal of Learning Disabilities, 1977)
Reports on the results of a study which asked college students to establish priorities for assigning tutorial help to children failing in school. Rating of the children on the basis of various combinations of sex, age, kind of behavior problem and subject of school difficulty; Variables selected for top and lower priorities.